Prediction of taxi drivers' safe-driving behaviors based on the theory of planned behavior: The role of habit - Asghar Razmara; Teamur Aghamolaei; Abdoulhossain Madani; Zahra Hosseini; Shahram Zare (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Safe-driving behaviors of taxi drivers are fundamental to health. The present research aimed to predict the taxi drivers' safe-driving behaviors based on the theory of planned behavior (TPB) and habit. MATERIALS AND METHODS: The present research is of a descriptive/analytical cross-sectional type conducted on 184 taxi drivers in Bandar Abbas who were selected through a multiple-stratified sampling method. Data collection instrument was a questionnaire comprised of two sections (demographic information and the constructs of TPB. STATISTICAL ANALYSIS USED: The data were later on analyzed via SPSS ver 19 and Pearson's correlation coefficient as well as multiple regressions. RESULTS: The mean age of the participants was 45.1 (standard deviation [SD = 11.1) years, and they had an average experience of taxi driving for 10.3 years (SD = 7.5). Subjective norms, perceived behavioral control, and habits were the predictors of one's intention of driving safely (r2 = 0.30, F = 18.7, P < 0.001). Moreover, attitude, perceived behavioral control, and habits were found to be the predictors of safe-driving behaviors (r2 = 0.19, F = 8.1, P < 0.001). Finally, habits showed to be a stronger predictor of safe-driving behaviors than attitude and perceived behavioral control. CONCLUSION: Consideration of individuals' behavioral habits and correction of unsafe habits, focus on the adverse effects of unsafe-driving behaviors, goal setting to change incorrect driving habits, attention to influential groups in altering unsafe-driving behaviors, and careful monitoring of abiding by the rules are suggested to promote safe-driving behaviors.